THE PERCEPTION OF PARENT'S ABOUT ONLINE LEARNING USING PROCESS EVALUATION MODEL IN TEJAKULA DISTRICT - Katarina Dewi Kurniawati (Universitas Islam Lamongan, 2022)
tis article made to evaluate the online learning process in Tejakula sub-district using the CIPPO model. This article was created based on data obtained related to the evaluation process of parents' perceptions of the online learning process that has been implemented.